Lung Maturation: The Survival Miracle of Very Low Birth Weight Infants - Alan H. Jobe (Pediatrics and Neonatology)
The increased survival of very preterm infants is generally attributed to improved care strategies. This review develops the thesis that the features of abnormal pregnancies responsible for very preterm deliveries also provide an explanation of why very preterm infants often survive. A normal fetus born at 24 weeks is very unlikely to survive. However, pregnancies that result in deliveries at 24 weeks are generally highly abnormal, and may have been so for prolonged periods prior to the preterm deliveries. Inflammatory or vascular developmental abnormalities resulting in very preterm birth can alter fetal development in such a way that organ system maturation is induced. This is supported clinically by the relative lack of very preterm infants with respiratory distress syndrome. Interventions such as antenatal corticosteroid treatment and postnatal surfactant treatment for infants with respiratory distress syndrome and gentle ventilation strategies maximize fetal adaptations to the abnormal fetal environment and improve outcomes.